The Urgency of BMT in Building Economic Independence in Islamic Boarding School Communities in Gresik - Alya Roghibah Faradisy; Sutono Sutono (Indonesian Economic Review, 2026)
Baitul Maal wat Tamwil (BMT) is a sharia microfinance institution that has a strategic role in supporting the economic independence of Islamic boarding school communities. This study aims to conceptually analyze the urgency of BMT in building the economic independence of Islamic boarding school communities in Gresik Regency. The research method used is a descriptive qualitative approach with a literature study method. Data were obtained from textbooks, articles, scientific journals, research reports, and online media. The results of the discussion indicate that BMT plays an important role through its tamwil function in providing financing for productive businesses for Islamic boarding schools, students, and the surrounding community, as well as its maal function in managing zakat, infaq, and alms funds for the economic empowerment of the community. However, optimizing the role of BMT still faces various obstacles, especially in the aspects of unintegrated regulations, limited human resources, capital, and suboptimal sharia governance and supervision. Therefore, a strategy is needed to strengthen the role of BMTs through institutional improvements, human resource enhancements, integration with Islamic boarding school business units, optimization of social functions, increased Islamic financial literacy, and enhanced collaboration with the government and related institutions. With this strengthening, BMTs are expected to become a key pillar in realizing Islamic boarding school economic independence and contribute to strengthening the local Sharia-based economy in Gresik Regency.